Modelos de negócios orientados para a sustentabilidade em empresas industriais brasileiras - Maffini, Clarissa Antonello (2023)
Organizations have been adopting a new stance towards society, especially with the aim of mitigating the impact of their activities and this new stance can be achieved considering sustainable and innovative criteria related to business models. Considering this scenario, the present study aimed to analyze sustainable innovation practices and the characteristics of sustainable business models in industrial companies. Sustainable innovation practices were analyzed based on the archetypes proposed by Bocken et al. (2014) and Ritala et al. (2018) and regarding to the characteristics of business models, it was be based on studies by Boons and Lüdeke-Freund (2013), Kiron et al., (2013a) and Taran; Boer; Lindgren (2015). This work has academic, theoretical and practical relevance as it has an integrated approach, which seeks to include new sustainable practices with the aim of innovating the business model and creating sustainable value for industrial companies. To this end, the study has a descriptive approach, quantitative nature and was operationalized through a survey. The sample selected for the investigation was defined based on the Ecoinovar research group's contact database, made up of 14,031 Brazilian industrial companies, which belong to a varied range of sectors. All companies subject to the study were contacted, and the sample consisted of companies that actually received, responded to and returned the duly completed questionnaires. The results pointed to a positive and significant effect between innovation practices aimed at sustainability and sustainable business models. The evidence revealed a positive and significant effect between sustainability-oriented innovation practices and the degree of innovation present in sustainable business models. The analyzes reflected that the pandemic did not result in significant changes to sustainable business models in terms of the degree of innovation or the configuration itself, indicating a possible stability and resistance of these companies in the face of disruptions resulting from the pandemic.